2004
DOI: 10.1111/j.1740-0929.2004.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of feed intake, digestibility and fattening performance of Brahman grade cattle (Bos indicus) and crossbred water buffalo (Bubalus bubalis)

Abstract: Twenty growing crossbred cattle and crossbred water buffalo (carabao) with an average age of 22 (18–24 months) months were equally distributed into two treatment groups according to species. The animals were fed with the same ration made up of corn silage (50%) + wet brewer's spent grain (30%) + concentrate mixture (20%), and their fattening performance was monitored. The digestibilities of the different nutrients were likewise determined. The economics of raising the animals under intensive production system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 7 publications
2
24
2
Order By: Relevance
“…The coefficient of whole tract apparent digestibility of DM and OM was not affected by N source in either animal species. But whole tract apparent digestibility of NDF was significantly higher in both animal species when urea‐N in the diet was fed as the main source of N. The digestibility of DM (buffalo 0.74–0.77 and cattle 0.78–0.78), OM (buffalo 0.75–0.78 and cattle 0.79–0.80) were similar in both animal species, and this was in agreement with reports by Lapitan et al . (2004) and Liang and Young (1995) who found no significant differences in DM and OM digestion when comparing buffaloes and cattle.…”
Section: Discussionsupporting
confidence: 92%
“…The coefficient of whole tract apparent digestibility of DM and OM was not affected by N source in either animal species. But whole tract apparent digestibility of NDF was significantly higher in both animal species when urea‐N in the diet was fed as the main source of N. The digestibility of DM (buffalo 0.74–0.77 and cattle 0.78–0.78), OM (buffalo 0.75–0.78 and cattle 0.79–0.80) were similar in both animal species, and this was in agreement with reports by Lapitan et al . (2004) and Liang and Young (1995) who found no significant differences in DM and OM digestion when comparing buffaloes and cattle.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Granum et al (2007) observed that the intake at pasture, in terms of per cent of BW, is higher in Swamp buffaloes than in cattle. Lapitan et al (2004) observed that the apparent digestibility of organic matter in Swamp buffaloes was 70%. However, no studies are available on the effect of grazing on organic matter digestibility in river buffaloes.…”
Section: Introductionmentioning
confidence: 99%
“…This study is part of experiments conducted to compare the growth and fattening performance and meat characteristics of crossbred cattle and buffaloes of a similar age and nutritional status (Lapitan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%